Nematode Management in Florida Vegetable and Ornamental Production. (1st August 2014) - Kokalis-Burelle, Nancy; Iriarte, Fanny; Butler, David; Hong, Jason; Rosskopf, Erin
Commercial vegetable and ornamental crop production occurs in humid sub-tropical to tropical climates throughout the Florida peninsula. Historically, the majority of soil fumigants used in vegetable and fruit crops in Florida are applied to tomato, pepper, and strawberry, with cut flowers and caladiums accounting for significant fumigant use in ornamental production. Root-knot nematodes (Meloidogyne spp.) cause severe galling and necrosis on roots of most vegetable and ornamental crops grown in Florida. In addition to crop plants, many weeds are susceptible to these nematodes, and harbor nematode populations between crops. Root-knot nematodes cause severe root disease, restricting water and nutrient uptake, and providing entry points for other soil-borne pathogens. Increasing restrictions on chemical soil fumigants have necessitated the development of new options for plant parasitic nematode management in vegetable and ornamental crop production. Currently, all soil fumigants registered in the U.S. face regulatory limitations by the EPA based on their potential for by-stander exposure and concerns related to volatile organic compounds (VOCs). Nematode control is highly correlated to weed control, therefore, integrated control of both types of pests provides the greatest chance for success. USDAARS researchers with their collaborators are developing new tactics to manage both nematodes and weeds in vegetable and ornamental crop production systems. These tactics include the low-risk chemical 'SPK', steam, and anaerobic soil disinfestations (ASD), and these approaches are often integrated into site-specific management plans. The low-risk chemical SPK is a unique formulation of organic acids with efficacy against root-knot nematodes (Meloidogyne spp.), weeds, and soil-borne plant pathogenic fungi and bacteria. This material is a non-fumigant and poses minimal risk to the environment, applicators, and by-standers. Steam is another effective method for broad-spectrum soil-borne pest control including nematodes, weeds, and fungal pathogens. However, logistics and expense of steam application require more research and may limit adoption in the short-term. ASD uses a combination of solarization to raise soil temperatures, organic amendments to stimulate microbial activity, and soil saturation to create anaerobic conditions in soil. In multiple field trials in Florida, ASD has reduced plant-parasitic nematodes in soil compared to solarization alone, and has provided excellent weed control in raised-bed vegetable production systems. While integrated nematode and weed control tactics are preferred, stand-alone approaches that can be incorporated into production systems are also being investigated for nematode control. These approaches include vegetable grafting and biological control with the nematode-parasitic bacterium Pasteuria penetrans. Grafting for root-knot nematode control in tomato has been successful in reducing nematode populations in roots and soil, and has improved yield in melon compared to non-grafted plants. Greenhouse and microplot trials on P. penetrans are ongoing while initial results indicate good potential for field application of this new biological control agent.